Hubungan Adversity Quotient dan Dukungan Sosial Dengan Optimisme Akademik Pada Siswa SMP Negeri 1 Wanadadi - Wardani, Ita Anindya; Sugiharto, Dwi Yuwono Puji (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
The Relationship Between Adversity Quotient and Social Support with Academic Optimism for Students of SMP Negeri 1 Wanadadi. The porpose of this research was to examine the relationship of adversity quotient and social support with academic optimism of junior high school 1 Wanadadi. This research used quantitative research methods. The research subjects were 234 students of junior high school 1 Wanadadi. The data were collected using learning academic optimism scale, adversity quotient scale and social support scale. The data were analyzed using product moment correlation. The result showed the value of correlation coefficient of 0,479 with a probability level of 0,000 (p<0,05) it's meaning that there is a significant relation adversity quotient and social support with academic optimism of junior high school 1 Wanadadi. Positive value indicates the higher adversity quotient and social support, the higher the academic optimism.Keyword: Academic Optimism, Adversity Quotient, And Social Support